2018
DOI: 10.1121/1.5054015
|View full text |Cite
|
Sign up to set email alerts
|

Passive guided waves measurements using fiber Bragg gratings sensors

Abstract: Guided elastic waves are often studied as an effective solution for Structural Health Monitoring (SHM) systems of plate-like structures thanks to the capacity to propagate on large distances. In typical applications such as monitoring delaminations in aircraft fuselage, a network made of piezoelectric transducer (PZT) is used to emit and receive such waves in the structure. Fiber Bragg grating (FBG) sensors on optical fibers are a promising alternative to PZT for guided waves measurements in practical applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Furthermore, sensors such as Fiber Bragg Gratings (FBG) on optical fibers, which are unable to emit waves, can be used (Betz et al, 2003). Those sensors have previously been successfully used in combination with piezoelectric transducers (PZT) for active a) arnaud.recoquillay@cea.fr data acquisition (Betz et al, 2003;Takeda et al, 2005), 30 and more recently for passive data acquisition using noise cross correlation to recover the active signal first in seismology (Zeng et al, 2017) and then at ultrasonic frequencies for metallic plates (Druet et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, sensors such as Fiber Bragg Gratings (FBG) on optical fibers, which are unable to emit waves, can be used (Betz et al, 2003). Those sensors have previously been successfully used in combination with piezoelectric transducers (PZT) for active a) arnaud.recoquillay@cea.fr data acquisition (Betz et al, 2003;Takeda et al, 2005), 30 and more recently for passive data acquisition using noise cross correlation to recover the active signal first in seismology (Zeng et al, 2017) and then at ultrasonic frequencies for metallic plates (Druet et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of ambient noise cross-correlation and Fiber Bragg Gratings sensors, described in (Druet et al, 2018), allows for the determination of the pitchcatch response, that is the response of the structure for a…”
mentioning
confidence: 99%
“…Indeed, in the past years researchers have shown that it is possible to use ambient structure-borne elastic noise instead of actively emit the waves in the structure in order to retrieve the impulse response of the medium between two sensors (Sabra et al, 2007a). Moreover, it has been shown in (Druet et al, 2018) that passive guided wave measurements are possible thanks to the coupling between FBGs and passive methods. In this paper is shown how to perform passive tomography by coupling guided wave tomography adapted to SHM framework (Druet et al, 2019) with passive methods.…”
Section: Introductionmentioning
confidence: 99%
“…This method is transposed for pipe structures in [5]. It has also be shown in [6] that passive guided waves measurements using FBG sensors is possible thanks to passive methods such as the ambient noise cross-correlation. In this paper the studies are focused on the impacts that have the fiber Bragg Gratings measurements on guided wave tomography imaging on pipe structure because of the FBG directivity.…”
Section: Introductionmentioning
confidence: 99%